JMZ-12, a disordered AEI / CHA family zeolite, its synthesis and use

CN116829506BActive Publication Date: 2026-10-30JOHNSON MATTHEY PLC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280014369.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-04
Filing Date
2022-02-28
Publication Date
2026-10-30
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

虽然一些催化剂在某些条件下可表现良好,但仍需要在暴露于非常高的温度后实现高催化活性的更水热稳定并且稳健的沸石

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116829506B_ABST
    Figure CN116829506B_ABST
Patent Text Reader

Abstract

The present invention relates to a method of making a synthetic crystalline material designated JMZ-12 having a framework composed of disordered AEI and CHA structures, substantially free of framework phosphorus and preferably made in the absence of halide such as fluoride ions. Such a method includes the step of heating a reaction mixture under crystallization conditions for a sufficient period to form a disordered zeolite having both CHA and AEI topology, wherein the reaction mixture comprises at least one source of aluminum, at least one source of silicon, a source of alkali or alkaline earth cations, and a structure directing agent comprising a molar ratio of at least one source of quaternary ammonium cations and at least one source of alkyl-substituted piperidinium cations of from 0.20 to about 1.4. The resulting zeolite can be used as a catalyst, particularly when used in combination with exchanged transition metals and optionally rare earth metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing synthetic crystalline materials. Specifically, this invention relates to a method for preparing a synthetic material named JMZ-12, as well as their synthesis and use in catalyst compositions, the synthetic material having a structure composed of disordered AEI and CHA structures. Background Technology

[0002] Zeolites are crystalline or quasi-crystalline aluminosilicates composed of repeating SiO4 and AlO4 tetrahedral units linked by oxygen atoms at their vertices. These tetrahedral units and their connections form various structural units that can be arranged in multiple ways to form a molecular framework, also known as a topological structure. The regular and repeating connection of these frameworks creates molecular-dimensional cavities and channels within the crystal, thus generating microporosity in the zeolite. The spatial relationships resulting from the regular repetition of these molecular frameworks also produce different crystal morphologies. More generally, other tetrahedral structures such as phosphates can be combined with AlO4 and optionally SiO4 to form other types of molecular sieves such as aluminosilicate phosphate (SAPO) or aluminosilicate phosphate (AlPO).

[0003] Many types of synthetic zeolites have been synthesized, each possessing one or more unique frameworks based on a specific arrangement of its tetrahedral units. By convention, the International Zeolite Association (IZA) assigns unique three-letter codes (e.g., “CHA” and “AEI”) to each framework type. These zeolites can be ordered or disordered. Ordered zeolites (e.g., regular crystalline solids) are periodically ordered crystal structures in three dimensions. These structures are classified based on their repeating periodic structural units (PerBU), and if a periodic ordering occurs in all three dimensions, it can be called an “end-member structure.” Disordered molecular sieves, on the other hand, exhibit periodic orders with dimensions less than 3, such as 0, 1, or 2 dimensions. In disordered structures, the stacking order of PerBU deviates from the periodic ordering. This can also be interpreted as structurally invariant PerBU structural or stacking disorder. This disorder manifests as a single-crystal morphology.

[0004] The selected molecular sieves can exhibit disorder, including but not limited to stacking disorder, planar stacking faults, and phase coexistence. These types of disorder are not mutually exclusive. In layered structures with stacking disorder, a single framework type may deviate from periodic ordering. Planar stacking faults in the framework structure may include, for example, a mirror image of the structure on either side of the plane (e.g., the "twin plane" phenomenon) or a rotation of one part of the crystal relative to another part in a particular plane. Phase coexistence may include a transformation from one framework structure to another. Zeolites may contain one or more types of disorder that result in any known or unknown disordered framework. Known disordered frameworks include, for example, zeolite β (BEA) and the AEI / CHA coexistence.

[0005] The crystallization process of zeolites cannot be fully described solely by classical variables such as reactant composition, temperature, and pressure. Crystallization also involves polymerization-depolymerization, dissolution-precipitation, nucleation-crystallization, and other complex phenomena encountered in aqueous colloidal dispersions. Specific zeolite topologies are based on the interaction between a structure-directing agent (SDA) (also known as a “template” or “templator”) and the chemical properties of the reaction mixture (e.g., all other reaction parameters controlling the reaction mixture, such as oxide composition, temperature, time, reagent type, and pH). SDAs are typically complex organic molecules that guide or direct the molecular shape and patterning of the zeolite framework. Generally, SDAs are used to position hydrated silica and alumina and / or act as a mold around which zeolite crystals form. After crystal formation, the SDA is removed from the internal structure of the crystal, leaving behind a molecularly porous aluminosilicate cage.

[0006] Several techniques for synthesizing zeolite composites are known. For example, U.S. Patent No. 7,704,487 describes the use of diethylenetriamine as a template for the synthesis of zeolite BEA, and U.S. Patent No. 5,139,759 discloses the synthesis of zeolite β using diethanolamine and tetraethylammonium bromide. U.S. Patent No. 6,812,372 describes the synthesis of SAPO AEI / CHA composites using tetraethylammonium hydroxide (TEAOH) as a template in the presence of phosphoric acid, alumina, and silica. U.S. Patent No. 7,094,389 discloses the synthesis of large crystalline aluminosilicate AEI / CHA composites using two different structure-directing agents, one for the synthesis of CHA framework molecular sieves and the other for the synthesis of AEI framework molecular sieves.

[0007] Molecular sieves have numerous industrial applications. For example, light olefins, particularly ethylene and propylene, can be produced by contacting feedstocks containing oxygen-containing organic compounds such as methanol or dimethyl ether with catalysts containing SAPO and / or AlPO. Aluminosilicate zeolites have been used to address NO present in the exhaust gases of internal combustion engines, gas turbines, coal-fired power plants, etc. x Selective catalytic reduction (SCR) catalysts. Preferred SCR catalysts are those that exhibit high activity over a wide operating temperature range and retain their high activity after exposure to very high temperatures. While some catalysts perform well under certain conditions, there is still a need for more hydrothermally stable and robust zeolites that achieve high catalytic activity after exposure to very high temperatures.

[0008] This invention solves this problem and others by providing improved zeolites with high catalytic performance, catalysts made from such zeolites, and methods for synthesizing such zeolites. Summary of the Invention

[0009] A novel zeolite synthesis method for producing zeolites with excellent catalytic performance has been discovered. More specifically, a novel disordered AEI / CHA zeolite, named JMZ-12 throughout this document, can be synthesized using a combination of two SDAs containing a quaternary ammonium cation (Q) and an alkyl-substituted piperidinium (P) cation in a molar ratio (Q / P) of about 0.20 to about 1.4, preferably in the absence of halides such as fluorides. When copper exchange is included, the resulting JMZ-12 zeolite exhibits superior SCR catalytic performance, particularly after hydrothermal aging, compared to copper-exchanged CHA zeolite and copper-exchanged AEI zeolite. x Conversion rate and N2O selectivity.

[0010] Accordingly, a method for synthesizing zeolites is provided, the method involving heating a reaction mixture under crystallization conditions for a sufficient period of time to form disordered zeolites having both CHA and AEI topologies, wherein the reaction mixture comprises at least one aluminum source, at least one silicon source, an alkaline or alkaline earth cation source, and a structure directing agent comprising at least one quaternary ammonium cation (Q) source and at least one alkyl-substituted piperidinium cation (P) source with a molar ratio Q / P of about 0.20 to about 1.4.

[0011] JMZ-12 zeolite synthesized by the method described herein is also provided.

[0012] Also provided are disordered zeolites with a d50 crystal size of less than 0.5 micrometers and a main phase having CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of about 95:5 to about 5:95.

[0013] Also provided is a disordered zeolite comprising a main phase of CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of about 95:5 to about 5:95; and a CHA-rich surface layer topology and an AEI-rich internal topology.

[0014] Also provided is a disordered zeolite comprising a main phase of CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of about 95:5 to about 5:95; and a surface SAR and a main SAR, wherein the surface SAR is lower than the main SAR.

[0015] It also provides a method for selectively reducing NO. xA catalyst composition comprising: a JMZ-12 zeolite having a CHA and AEI topology as the main phase, wherein the CHA and AEI topology is present in a molar ratio of about 95:5 to about 5:95, having a d50 crystal size of less than 0.5 micrometers, and having a silica to alumina ratio (SAR) of about 10 to about 25; and one or more exchanged transition metals selected from copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), molybdenum (Mo), and zinc (Zn), wherein the zeolite and the one or more exchanged transition metals are present in a weight ratio of about 100:1 to about 20:1. The catalyst composition may also optionally contain one or more rare earth metals.

[0016] A catalyst article is also provided, comprising: a plurality of walls of a honeycomb flow-through substrate or wall-flow filter; and a JMZ-12 zeolite catalyst coated on and / or within at least a portion of the walls, wherein (i) the JMZ-12 zeolite catalyst has a main phase with CHA and AEI topologies present in a molar ratio of about 95:5 to about 5:95; (ii) the JMZ-12 zeolite catalyst has a d50 crystal size of less than 0.5 micrometers and has a silica to alumina ratio (SAR) of about 10 to about 25; and (iii) one or more exchanged transition metals selected from copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), molybdenum (Mo), and zinc (Zn), wherein the zeolite and the one or more exchanged transition metals are present in a weight ratio of about 100:1 to about 20:1. Attached Figure Description

[0017] Figure 1 Powder X-ray diffraction (XRD) patterns of the following prepared (SDA-containing) JMZ-12 samples are shown: a) Example 1; b) Example 2; c) Example 3; d) Example 4; e) Example 5.

[0018] Figure 2 A scanning electron microscope (SEM) image of the JMZ-12 prepared in Example 2 is shown.

[0019] Figure 3 The JMZ-12 prepared in Example 2 is shown. 13 The 1000-magic-angle rotating nuclear magnetic resonance (MAS NMR) spectrum shows that the two SDAs used for synthesis were still encapsulated in the zeolite at the end of crystallization.

[0020] Figure 4The surface SAR measured by synchrotron X-ray photoelectron spectroscopy (SR-XPS) is shown. A depth profile of JMZ-12 zeolite (Example 2) with an AEI / CHA co-occurrence ratio of 67 / 33 was obtained. The bulk SAR of this sample was measured to be 16 by XRF.

[0021] Figure 5 The powder X-ray diffraction (XRD) patterns of the selected activated JMZ-12 samples (H-form) are shown compared to those of pure AEI and CHA: a) pure AEI; b) Example 2; c) Example 3; d) Example 4; e) Example 5; f) pure CHA. All XRD patterns were collected in hydrated form.

[0022] Figure 6 A comparison of powder X-ray diffraction (XRD) patterns is shown for a) activated JMZ-12 corresponding to the AEI / CHA 50 / 50 commensal from Example 3 and b) a 50 / 50 physical mixture of CHA and AEI zeolite. Both XRD patterns were obtained in hydrated form.

[0023] Figure 7 The results show that, compared to pure copper AEI and copper CHA zeolite, fresh copper JMZ-12 (H-form Example 2) is effective against NO. x Selective catalytic reduction (SCR) of NO x Conversion rate.

[0024] Figure 8 The results show that, compared to pure copper AEI and copper CHA zeolite, fresh copper JMZ-12 (H-form Example 2) is effective against NO. x The N2O selectivity of selective catalytic reduction (SCR).

[0025] Figure 9 The results show that, compared to pure copper AEI and copper CHA zeolite, copper JMZ-12 (H-form Example 2) is effective against NO. x Selective catalytic reduction (SCR) of NO x Conversion rate. All samples were aged at 750°C for 80 hours.

[0026] Figure 10 The results show that, compared to pure copper AEI and copper CHA zeolite, copper JMZ-12 (H-form Example 2) is effective against NO. x Selective catalytic reduction (SCR) of NO x Conversion rate. All samples were aged at 900℃ for 5 hours.

[0027] Figure 11 The results show that, compared to pure copper AEI and copper CHA zeolite, fresh copper JMZ-12 (H-form Example 2) is effective against NO.x The N2O selectivity of selective catalytic reduction (SCR) was observed. All samples were aged at 750°C for 80 hours.

[0028] Figure 12 The results show that after aging at 900°C for 5 hours, copper JMZ-12 (H-form Example 2) exhibits better performance against NO compared to two pure AEI zeolites with different SARs. x Selective catalytic reduction (SCR) of NO x Conversion rate.

[0029] Figure 13 The results show that after aging at 900°C for 5 hours, copper JMZ-12 (H-form Example 2) exhibits better performance against NO compared to two pure AEI zeolites with different SARs. x The N2O selectivity of selective catalytic reduction (SCR).

[0030] Figure 14 The results show that, compared to pure copper JMZ-12 (all JMZ-12, H-form Example 5), copper and yttrium JMZ-12 have a lower NO content. x Selective catalytic reduction (SCR) of NO x Conversion rate. Both samples were tested in their fresh state and after aging at 850°C for 16 hours.

[0031] Figure 15 The results show that, compared to pure copper JMZ-12 (all JMZ-12, H-form Example 5), copper and yttrium JMZ-12 have a lower NO content. x The N2O selectivity of selective catalytic reduction (SCR) was measured. Both samples were tested in their fresh state and after aging at 850°C for 16 hours. Detailed Implementation

[0032] The synthesis technique of this invention enables the production of a novel disordered zeolite family, JMZ-12, with a structure of disordered symbiotic organisms based on the topology of AEI and CHA. This synthesis technique typically utilizes a reaction mixture comprising water, a silica source, an alumina source, and two structure-directing agents (SDAs), each comprising a quaternary ammonium component (Q) and an alkyl-substituted piperidinium component (P). Preferably, the two components of the SDA are present in the structure-directing agent at a molar ratio of Q / P of about 0.20 to about 1.4. Upon heating under conditions suitable for crystal formation, solid disordered AEI / CHA zeolite crystals are produced.

[0033] As used herein, the term "zeolite" refers to a crystalline or quasicrystalline aluminosilicate molecular sieve with open channels and exchangeable cations. Therefore, the term "zeolite" refers to aluminosilicates as a specific subclass of molecular sieves and excludes other types of molecular sieves such as aluminophosphate (AlPO) and aluminosilicate phosphate (SAPO).

[0034] As used herein, the term “CHA” refers to a CHA-type topology or framework as identified by the International Zeolite Association (IZA) Structure Commission, and the term “CHA zeolite” means an aluminosilicate in which the main crystalline phase is CHA.

[0035] As used herein, the term “AEI” refers to an AEI-type topology or framework as identified by the International Zeolite Association (IZA) Structure Commission, and the term “AEI zeolite” means an aluminosilicate in which the main crystalline phase is AEI.

[0036] As used herein, the term "disordered AEI / CHA zeolite" refers to a zeolite in which the main crystalline phases are a combination of AEI and CHA topologies.

[0037] As used herein, the term “AEI / CHA zeolite symbiosis” refers to disordered AEI / CHA zeolite that has a CHA topology and an AEI topology in a region at the submicroscopic scale (i.e., below 100 nm) and within a single crystal phase or as a single crystal morphology.

[0038] The relative proportions of each coexisting phase can be analyzed by X-ray diffraction, and particularly by comparing observed patterns with computationally generated patterns using algorithms to simulate the effects of stacking disorder. DIFFaX is a Fortran computer program based on a mathematical model for calculating intensities from crystals containing planar faults (Treacy, MMJ; Newsam, JM; Deem, MW: A general recursion method for calculating diffracted intensities from crystals containing planar faults. Proc. R. Soc. London Ser. A 433 (1991) 499–520). DIFFaX is a simulation program selected by and available from the International Zeolite Association for simulating powder XRD patterns of random coexisting phases (see “Collection of Simulated XRD Powder Patterns for Zeolites”, 5th revised edition, Elsevier, 2007, published on behalf of the International Zeolite Association's Structure Committee). DIFFaX has been used in theoretical studies of zeolite β (Treacy et al., 1991), AEI-CHA commensal organisms in numerous patents, and many other commensal organisms in zeolites and other materials.

[0039] Once the desired crystallization is complete, the solid precipitate containing zeolite crystals can be separated from the mother liquor, which can then be discarded or recycled. Preferably, the separated zeolite crystals are treated to remove residual SDA from their crystal structure, followed by one or more additional processing steps, such as washing, purification, drying, calcination, and conditioning, to produce disordered AEI / CHA zeolite materials (JMZ-12 family) with the desired physical and chemical properties. Additional processing steps may include non-metallic ion exchange to produce JMZ-12 zeolite in ammonium or proton form. JMZ-12 zeolite can also undergo post-synthetic treatment, such as incorporation of catalytically active metals via ion exchange to further enhance catalytic performance.

[0040] The alkyl-substituted piperidinium (P) component of SDA is preferably a piperidinium having two alkyl groups attached to a nitrogen ring and one or two additional alkyl groups at the -2-, -3-, or -6-ring positions. Preferably, the alkyl group is methyl, ethyl, or a combination thereof. For example, suitable alkyl-substituted piperidinium compounds include N,N-dimethyl-3,3-dimethylpiperidinium, N,N-methylethyl-3,3-dimethylpiperidinium, N,N-dimethyl-2-methylpiperidinium, N,N-dimethyl-2,6-dimethylpiperidinium, N,N-diethyl-2,6-dimethylpiperidinium, N-ethyl-N-methyl-2,6-dimethylpiperidinium, and combinations thereof in non-halogenated forms. Most preferably, the alkyl-substituted piperidinium is N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (3,5-DMDMPOH). Preferably, the alkyl-substituted piperidinium component is not in halide form, for example, not N,N-dimethyl-3,5-dimethylpiperidinium fluoride, N,N-dimethyl-3,5-dimethylpiperidinium bromide, N,N-dimethyl-3,5-dimethylpiperidinium iodide, or N,N-dimethyl-3,5-dimethylpiperidinium chloride.

[0041] The quaternary ammonium component (Q) of the SDA is preferably acyclic, and more preferably a tetraalkylammonium compound, such as tetraethylammonium hydroxide (TEAOH) or tetraethylammonium acetate. Most preferably, the template is tetraethylammonium hydroxide. Preferably, the quaternary ammonium component is not in halide form, i.e., not tetraethylammonium fluoride, tetraethylammonium bromide, or tetraethylammonium chloride.

[0042] The alkyl-substituted piperidinium component (P) and quaternary ammonium (Q) component of SDA are preferably present in a molar ratio of about 0.20 to about 1.4, Q / P. For example, the molar ratio of quaternary ammonium to alkyl-substituted piperidinium can be 0.30, 0.45, 0.63, 1, etc. It has been found that the molar ratio of quaternary ammonium to alkyl-substituted piperidinium can be adjusted to obtain different members of the JMZ-12 family of zeolites (containing different degrees of disorder between pure AEI and CHA structures). For example, relatively high amounts of 3,5-DMDMPOH produce AEI-rich disordered zeolites, and relatively high amounts of TEAOH produce CHA-rich disordered zeolites. However, molar ratios outside these ranges tend to form zeolite compositions rather than commensal compositions.

[0043] The reaction mixture used to form JMZ-12 is preferably free of or substantially free of halogens, including fluorine. A substantially halogen-free JMZ-12 zeolite has less than 1 ppm of halogen. A halogen-free JMZ-12 zeolite has less than 0.5 ppm of halogen or no detectable halogen. In most industrial applications, the presence of fluorine or other halogens in the synthesis medium and / or the resulting zeolite crystals is undesirable due to the highly corrosive and hazardous nature of hydrofluoric acid or fluorinated derivatives that may be present in the reactive mixture or intermediates. The presence of halogens such as fluorine can also adversely affect the desired silica-to-alumina ratio (SAR) of the resulting disordered zeolite, as fluoride ions interfere with aluminum incorporation into the crystal lattice. High SAR zeolites tend to be more thermally stable, but low levels of available alumina sites limit the introduction and stabilization of catalytically active metals such as copper. Therefore, low amounts of aluminum in the crystal lattice may hinder the preparation of zeolites for applications such as NO removal from exhaust gases. x The JMZ-12 zeolite catalyst is an effective copper-exchange catalyst for selective catalytic reduction (SCR) applications.

[0044] The reaction mixture used to form JMZ-12 is preferably free of or substantially free of source phosphorus. JMZ-12 zeolite substantially free of framework phosphorus has less than 1 ppm of phosphorus. JMZ-12 zeolite free of framework phosphorus has less than 0.5 ppm of phosphorus or undetectable phosphorus. The zeolite of the present invention is not a silicate aluminophosphate (SAPO), and therefore does not have a considerable amount of phosphorus in its framework. That is, the zeolite framework does not have phosphorus as a regular repeating unit and / or does not have an amount of phosphorus that will affect the fundamental physical and / or chemical properties of the material, particularly relative to the material's ability to selectively reduce NOx over a wide temperature range.

[0045] Suitable silica sources include, but are not limited to: sodium silicate; fumed silica; silicates; precipitated silica; colloidal silica; silica gel; silica hydrogel; silicic acid; tetraalkyl orthosilicate; aluminosilicate zeolites with an SAR of less than 15, preferably less than 10; dealubilized zeolites such as dealubilized zeolite Y; and silicon hydroxides and alkoxides. When the zeolite is the silica source, the cation type can be selected from sodium-type (Na-type), proton-type (H-type), etc. + It is at least one type from the group consisting of proton-type and ammonium-type (NH4-type), wherein the proton-type is preferred. A silica source with a high relative yield is preferred.

[0046] Suitable alumina sources include sodium aluminate, aluminates, alumina, zeolites, alumina colloids, boehmite, pseudoboehmite, aluminum hydroxide, aluminum salts such as aluminum sulfate and aluminum chloride, aluminum hydroxide and alkoxides, and alumina gel. Preferably, the alumina source is an aluminosilicate zeolite or its derivatives. Preferred zeolites include octahedral zeolite (FAU), zeolite Y, and zeolite X, with FAU being the most preferred. Preferably, the molar ratio of silica to alumina in these zeolites should be from about 2 to about 20, more preferably from about 2 to about 10, and most preferably from about 5 to about 10. When the zeolite is the alumina source, the cation type can be selected from sodium type (Na type), proton type (H type), etc. + It is at least one type from the group consisting of proton-type and ammonium-type (NH4-type), wherein the proton-type is preferred. A high relative yield alumina source is preferred.

[0047] Both the silica and alumina sources can be derived from zeolites, i.e., the silica source is a zeolite with a high SAR (e.g., greater than 100), and the alumina source is a zeolite with a low SAR (e.g., less than 10). Other examples of the combined use of alumina and silica sources include zeolite alumina sources such as FAU, and silica sources selected from sodium silicate, fumed silica, and colloidal silica.

[0048] The reaction mixture preferably includes an alkali metal source, such as one or more metals selected from sodium, potassium, cesium, and lithium. The alkali metal can be in the form of, for example, hydroxides (e.g., sodium hydroxide (NaOH) or potassium hydroxide (KOH)), oxides (e.g., sodium oxide (Na₂O) or potassium oxide (K₂O)), carbonates, sulfates, nitrates, acetates, silicates, aluminates, carboxylates, and combinations of two or more of these. Preferred sources include alkali metal hydroxides such as NaOH, and alkali metal oxides such as sodium oxide (Na₂O) and potassium oxide (K₂O). When used as an alumina source, the alkali metal can also be supplied via zeolite. Furthermore, when the silica and alumina sources contain alkali metals, the alkali metal can also act as an alkali source. Preferably, the alkali metal component is not in halide form, i.e., not a fluoride, bromide, or chloride of sodium, potassium, cesium, or lithium.

[0049] Purified water can be used as water, but it can also be used to prepare the raw materials in the form of an aqueous solution.

[0050] The reaction mixture preferably has the following composition:

[0051] ● The molar ratio of silicon dioxide to aluminum oxide (SiO2 / Al2O3 ratio) is about 10 to about 100, for example about 55 and about 75;

[0052] ● The molar ratio of alkali metal oxides to silicon dioxide (X2O / SiO2 ratio, where X = Na, K, Cs, Li) is about 0.01 to about 0.5, for example, about 0.01 to about 0.3;

[0053] ● The molar ratio of SDA to silicon dioxide (SDA / SiO2 ratio) is about 0.01 to about 0.5, for example, about 0.05 to about 0.2;

[0054] ●The molar ratio of OH to silicon dioxide (OH / SiO2 ratio) is about 0.1 to about 0.9, for example, about 0.6 to 0.8;

[0055] ● The molar ratio of water (H2O) to silicon dioxide (H2O / SiO2 ratio) is about 3 to about 25, for example about 5 to about 15.

[0056] JMZ-12 zeolite crystals are formed by hydrothermal synthesis, which is preferably carried out in an autoclave or other sealed container under static or dynamic conditions at a temperature of 100°C to 200°C, preferably 120°C to 175°C, for a period of 0.5 to 10 days, preferably 18 to 96 hours.

[0057] Preferably, the reaction mixture produces high-purity disordered zeolite with little or no residual alumina source. For example, the crystallization process preferably consumes 90% to 100% by weight of an alumina source, such as 95% to 99% by weight, which is incorporated into the zeolite framework. Therefore, the reaction mixture and the resulting zeolite crystals may be free of or substantially free of alumina-based impurities, such as FAU zeolite. For example, the disordered AEI / CHA members of the resulting JMZ-12 family of zeolites may have less than 5% by weight of FAU zeolite, preferably less than 1% by weight, and even more preferably less than 0.1% by weight of FAU zeolite.

[0058] Preferably, the crystallization step does not involve the use of AEI or CHA seed crystals, as such crystals can reduce the purity of the resulting JMZ-12 zeolite, for example, by promoting the formation of a physical mixture of AEI and CHA zeolites instead of the desired disordered zeolite.

[0059] The precipitated zeolite crystals can be recovered using any well-known separation technique, such as decantation, filtration, ultrafiltration, centrifugation, or any other solid-liquid separation technique and combinations thereof. Preferred separation methods include mechanical separation, such as vacuum filtration. The recovered solids can then be washed with deionized or purified water and dried at elevated temperatures for several hours. The drying step can be carried out under vacuum or atmospheric pressure.

[0060] In the drying step, after the crystallization step or the washing step, moisture is removed from the zeolite. The conditions for the drying step are arbitrary, but an example is to dry the zeolite after the crystallization step or the washing step by placing it in an environment with a temperature of not less than 50°C and not more than 150°C for at least 2 hours, for example, 4 to 24 hours.

[0061] The method of the present invention may also include one or more steps to eliminate or extract organic contents (e.g., SDA or SDA byproducts) retained inside the zeolite cavity, such as heating the material to a temperature greater than 25°C, preferably between 100°C and 1000°C, for a period of time preferably from about 1 hour to 25 hours.

[0062] Zeolite materials can be calcined, preferably in an oxygen-containing environment such as air, at a temperature of about 450°C to 600°C, more preferably about 500°C to 550°C, for a period of about 2 to 10 hours, for example, about 5 to 7 hours.

[0063] After crystallization, JMZ-12 zeolite can have metal ions, such as alkali metal ions, at its ion exchange sites. In an optional ion exchange step, these alkali metal ions react with non-metallic cations, such as ammonium ions (NH4+). + ) or proton (H + Ion exchange with ammonium ions can be carried out by mixing zeolite into an aqueous solution of ammonium sulfate and then stirring. Furthermore, ion exchange with protons can be carried out by exchanging zeolite with ammonia ions and then calcining the zeolite.

[0064] In addition to the above-described synthesis techniques, this invention relates to novel disordered zeolites having at least two different micropore topologies, specifically CHA and AEI. These disordered AEI / CHA zeolites (JMZ-12 family materials) include crystals in which the total ratio of CHA to AEI topologies is from about 5:95 to about 95:5, preferably from about 60:40 to 40:60. In one exemplary embodiment, the molar ratio of AEI:CHA can range from about 5:95 to about 95:5. Examples of other topology ratios include 10:90, 15:85, 20:80, 25:75, 30:70, 40:60, 50:50, 60:40, 70:30, 75:25, 80:20, 85:15, and 90:10. The molar ratio of the topologies of the composition can be determined by analytical techniques such as X-ray diffraction (XRD) analysis. In particular, the topological molar ratio of the composition can be determined by DIFFaX analysis of the X-ray diffraction patterns collected on the dehydrated H-form of each sample.

[0065] The synthesis method described herein can produce high-purity JMZ-12 crystals, and preferably phase-pure ones. As used herein, the term "pure phase" means a disordered AEI / CHA zeolite (JMZ-12) in which AEI and CHA together constitute at least 95 mol% of the zeolite topology. For example, JMZ-12 contains at least 95 mol%, or even at least 97 mol%, of an AEI and CHA framework. In some embodiments, JMZ-12 is substantially free of other crystalline phases and frameworks. For example, JMZ-12 crystals synthesized by the method described herein may be substantially free of frameworks such as MOR, FAU, GME, AFX, AFT, and LEV. As used herein, the term "substantially free" means that JMZ-12 contains less than 1% of a zeolite framework different from CHA or AEI.

[0066] As used herein, SAR refers to the synthesized zeolite crystals and not the initial synthetic gel. The SAR of zeolite can be determined by conventional analysis. This ratio is intended to be as close as possible to the ratio in the rigid atomic framework of the zeolite crystals and to exclude silicon or aluminum in the binder or cations or other forms of silicon or aluminum present in channels. Since it may be difficult to measure the silica to alumina ratio (SAR) of zeolite directly after it has been combined with binder materials, particularly alumina binders, these silica to alumina ratios will be relative to the SAR of the zeolite itself (i.e., before the zeolite is combined with other catalyst components).

[0067] Disordered JMZ-12 crystals may have a bulk silica to alumina ratio (SAR) of about 10 to about 25, for example, about 12 to about 18, about 14 to about 16, about 10 to about 13, or about 21 to about 25. As used herein, the term “bulk SAR” refers to the SAR of the crystal or a crystal sample acquired as a whole. The bulk SAR of zeolites can be distinguished from their surface SAR.

[0068] The silica-to-alumina ratio (SAR) of the surface layer of JMZ-12 crystals can be lower than the SAR inside the crystal or the bulk SAR. As used herein, the term "surface layer" refers to a layer of zeolite extending from an outer flat surface to a specific depth of approximately 2 nm to approximately 12 nm. For example, the surface layer of a crystal is a layer extending from the outer flat surface of the crystal to a depth of 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, or 12 nm.

[0069] The ratio of surface SAR to main SAR can be from about 0.4 to about 0.95, for example, from about 0.5 to 0.7 or from about 0.8 to about 0.90. For example, the crystal can have about 5 to about 15 surface SAR and about 12 to about 18 main SAR. Other examples include about 5 to 8 surface SAR and about 13 to 16 main SAR, or about 12 to 14 surface SAR and about 14 to 18 main SAR.

[0070] JMZ-12 crystals may have a d50 crystal size of 0.5 micrometers or less, such as about 0.2 micrometers or less, about 0.1 micrometers or less, about 0.05 micrometers to about 0.5 micrometers, about 0.05 micrometers to 0.1 micrometers, or about 0.1 micrometers to about 0.25 micrometers. More preferably, JMZ-12 zeolite crystals may have a d90 crystal size of 0.5 micrometers or less, such as about 0.2 micrometers or less, about 0.1 micrometers or less, about 0.05 micrometers to about 0.5 micrometers, about 0.05 micrometers to 0.1 micrometers, or about 0.1 micrometers to about 0.25 micrometers. JMZ-12 crystals may have both the d50 and d90 values ​​as described above.

[0071] Crystal size is based on a single crystal, preferably a cubic or tetragonal crystal. Crystal size is the length of the longest diagonal of a three-dimensional crystal. Direct measurement of crystal size can be performed using microscopic methods such as SEM and TEM. For example, measurements via SEM involve examining the morphology of the material at high magnification (typically 1000x to 100,000x). The SEM method can be performed as follows: a representative portion of the zeolite powder is distributed on a suitable base such that individual particles are reasonably uniformly distributed across the entire field of view at magnifications of 1000x to 100,000x. From this group, statistically significant samples of random individual crystals (e.g., 50-200) are examined, and the longest diagonal of each individual crystal is measured and recorded. (Particles of significantly large polycrystalline aggregates should not be included in the measurements.) Based on these measurements, the d50 and d90 of the sample crystal size are calculated.

[0072] JMZ-12 zeolite can be used as a catalyst and / or adsorbent. In a preferred example of the catalyst composition, one or more catalytically active metals or metals that otherwise improve the performance of the catalyst composition (collectively, "reinforcing metals") are exchanged into JMZ-12. The exchange of reinforcing metals can be completed after zeolite synthesis via initial wet impregnation, solid-state ion exchange, or during the preparation of the carrier coating slurry, or in situ during the synthesis step by adding the reinforcing metal to the reaction mixture. Any of the aforementioned metals can be used in combination with any of the other methods, for example, to incorporate two or more reinforcing metals into the zeolite.

[0073] Preferably, the reinforcing metal is a non-framework metal. As used herein, a "non-framework metal" is a metal located within the pores of the zeolite and / or on at least a portion of the zeolite surface, preferably as an ionic substance, excluding aluminum, and excluding atoms constituting the framework of the molecular sieve. Preferably, the presence of the reinforcing metal facilitates the treatment of exhaust gases, such as exhaust gases from diesel engines, including substances such as NO. x Reduction, NH3 oxidation and NO x Storage method.

[0074] The reinforcing metals include certain transition metals such as copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), molybdenum (Mo), and zinc (Zn), preferably copper and / or iron, with copper being the most preferred. Some reinforcing metals are noble metals such as gold (Au) and silver (Ag), as well as platinum group metals such as platinum (Pt), palladium (Pd), ruthenium (Ru), and rhodium (Rh). Furthermore, the reinforcing metal can be one or more rare earth metals, such as cerium (Ce), praseodymium (Pr), neodymium (Nd), europium (Eu), erbium (Er), gadolinium (Gd), ytterbium (Yb), and yttrium (Y), which can be used to improve catalytic performance, particularly when used in combination with transition metals. (Although yttrium can be described as a transition metal, it is referred to herein as a rare earth metal due to its lanthanide-like properties.) Preferred rare earth metals include yttrium and erbium. In some examples, the JMZ-12 zeolite catalyst uses one or more transition metals in combination with one or more rare earth elements.

[0075] Preferably, transition metals are incorporated into JMZ-12 zeolite after synthesis via ion exchange. Rare earth metals are preferably incorporated into JMZ-12 in situ, after synthesis, or both. For example, cerium and yttrium can be incorporated into the zeolite via ion exchange after synthesis. Alternatively, yttrium can be incorporated in situ, and cerium can be incorporated via ion exchange after synthesis. Preferred catalysts, particularly those for treating waste gases, include JMZ-12 with exchanged copper and exchanged yttrium, exchanged copper and exchanged cerium, exchanged copper, exchanged yttrium and exchanged cerium, or exchanged copper, exchanged cerium and in-situ incorporated yttrium.

[0076] When two or more reinforcing metals are present in a JMZ-12 zeolite catalyst, each of these metals can be independently and locally concentrated at different locations within the zeolite crystal, or can have a concentration gradient within the crystal. For example, the JMZ-12 zeolite catalyst may have a relatively higher concentration of yttrium and / or erbium in the inner region of the crystal compared to the outer region, and a relatively higher concentration of copper and / or cerium, or both, in the outer region of the crystal compared to the inner region. As used herein, the “inner region” of a zeolite crystal means the inner 50% of the crystal by volume, and the “outer region” of a zeolite crystal means the outer 50% of the crystal by volume. For example, yttrium may be present in the inner and outer regions of the JMZ-12 crystal in a ratio of about 60:40, about 70:30, about 80:20, or about 90:10. Erbium may be present in the inner and outer regions of the JMZ-12 crystal in a ratio of about 60:40, about 70:30, about 80:20, or about 90:10. Copper may exist in the external and internal regions of JMZ-12 zeolite crystals in a ratio of approximately 60:40, 70:30, 80:20, or 90:10. Iron may exist in the external and internal regions of JMZ-12 zeolite crystals in a ratio of approximately 60:40, 70:30, 80:20, or 90:10. Cesium may exist in the external and internal regions of JMZ-12 crystals in a ratio of approximately 60:40, 70:30, 80:20, or 90:10.

[0077] One or more reinforcing metals are preferably present in the disordered zeolite material at a concentration of about 0.1 wt% to about 10 wt.% based on the total weight of the zeolite, for example, about 0.5 wt% to about 5 wt%, about 0.5 wt% to about 1 wt%, about 1 wt% to about 1.5 wt%, about 1 wt% to about 2 wt%, about 1 wt% to about 5 wt%, about 2.5 wt% to about 3.5 wt%, and about 3.5 wt% to about 5 wt%. For embodiments utilizing two or more reinforcing metals, each metal may be present independently in the amounts described above.

[0078] Based on the total weight of JMZ-12 zeolite, the concentration of these transition metals in the JMZ-12 zeolite material using a catalyst comprising copper, iron, or a combination thereof is preferably from about 1 wt% to about 5 wt%, more preferably from about 2.5 wt% to about 4.5 wt%. Based on the total weight of JMZ-12 zeolite, the catalyst using copper and rare earth metals such as yttrium preferably has a copper concentration of from about 1 wt% to about 5 wt%, more preferably from about 2.5 wt% to about 3.5 wt%, and a rare earth metal concentration of about about 2 wt%.

[0079] Based on the total weight of JMZ-12 zeolite, the concentration of these metals in JMZ-12 using yttrium and / or erbium catalysts is preferably from about 0.05 wt% to about 3 wt%, such as from about 0.1 wt% to 1 wt%, from about 0.5 wt% to 2 wt%, or from about 1 wt% to 2 wt%. In some embodiments, yttrium and / or erbium are used to enhance the performance of transition metals exchanged into the zeolite. Preferably, the presence of yttrium and / or erbium allows the amount of transition metal elements (such as copper) exchanged into JMZ-12 to be at least proportionally reduced, while similar catalytic performance can still be obtained compared to JMZ-12 zeolite where only copper is exchanged into the zeolite at higher loadings.

[0080] The cerium concentration in the catalyst material can be approximately 25 g / ft. 3 Approximately 550g / ft 3 Other ranges for Ce are: greater than 100 g / ft. 3 Greater than 200g / ft 3 Greater than 300g / ft 3 Greater than 400g / ft 3 Greater than 500g / ft 3 Approximately 75g / ft 3 Approximately 350g / ft 3 Including up to approximately 300g / ft 3 and approximately 100g / ft 3 Approximately 250g / ft 3 .

[0081] In some embodiments, the Ce concentration exceeds the theoretical maximum amount that can be used for exchange on the metal-promoted zeolite. Therefore, in some embodiments, Ce exists in more than one form, such as Ce ions, monomeric cerium dioxide, oligomeric cerium dioxide, and combinations thereof, provided that the oligomeric cerium dioxide is less than 5 μm, for example, having an average crystal size of less than 1 μm, about 10 nm to about 1 μm, about 100 nm to about 1 μm, about 500 nm to about 1 μm, about 10 nm to about 500 nm, about 100 nm to about 500 nm, and about 10 nm to about 100 nm. As used herein, the term "monomeric cerium dioxide" means CeO2 as a single molecule or portion, which is free on and / or within the zeolite or weakly bonded to the zeolite. As used herein, the term "oligomeric cerium dioxide" means nanocrystalline CeO2, which is free on and / or within the zeolite or weakly bonded to the zeolite.

[0082] In some examples, the catalyst composition is substantially free of certain catalytically active or reinforcing metals or metallic impurities. Regarding catalytically active or reinforcing metals, the term "substantially free" means that the material does not possess a significant amount of a particular metal. That is, the particular metal does not affect the fundamental physical and / or chemical properties of the material, particularly its selective reduction or storage of NO. x The amount of the ability exists. Exemplary catalyst compositions that are substantially free of catalytically active or reinforcing metals include catalyst compositions having a specified metal in amounts of less than 0.5 wt%, 0.1 wt%, 0.05 wt%, or 0.01 wt% based on the total weight of the catalyst composition.

[0083] The catalyst composition may be substantially free of any rare earth metals. Alternatively, the catalyst composition may be substantially free of rare earth metals other than yttrium, substantially free of rare earth metals other than yttrium and erbium, or substantially free of rare earth metals other than erbium.

[0084] The catalyst composition may be substantially free of any precious metals. Alternatively, the catalyst composition may be substantially free of precious metals other than palladium, platinum and rhodium, substantially free of precious metals other than palladium and platinum, or substantially free of precious metals other than palladium.

[0085] The catalyst composition may be substantially free of any non-framework transition metals. Alternatively, the catalyst composition may be substantially free of non-framework transition metals other than copper and iron. In some examples, the catalyst is substantially free of any non-framework transition metals other than copper.

[0086] It should be understood that the JMZ-12 zeolite catalyst, characterized as being substantially metal-free, may be free of any combination of metals excluded as described herein. For example, the catalyst composition may be substantially free of any non-framework transition metals other than copper and substantially free of rare earth metals other than yttrium, or substantially free of any non-framework transition metals other than copper and substantially free of rare earth metals other than erbium.

[0087] The metal-exchange JMZ-12 zeolite catalyst of the present invention is particularly suitable for heterogeneous catalytic reaction systems (i.e., solid catalysts in contact with gaseous reactants). To improve contact surface area, mechanical stability, and / or fluid flow characteristics, the catalyst can be disposed on and / or within a substrate (preferably a porous substrate). In some embodiments, a catalyst-containing support coating can be applied to an inert substrate, such as a corrugated metal plate or a honeycomb cordierite brick. Alternatively, the catalyst, together with other components such as fillers, binders, and reinforcing agents, can be kneaded into an extrudable slurry, which is then extruded through a die to form a honeycomb brick. Accordingly, the present invention provides catalyst articles comprising the JMZ-12 catalyst described herein coated on and / or within a substrate, or formed as an extruded catalyst body.

[0088] Certain aspects of the present invention provide catalytic support coatings designed for application onto a substrate. Support coatings comprising the JMZ-12 zeolite catalyst described herein are preferably solutions, suspensions, or slurries. Such support coatings may also contain non-catalytic components, such as fillers, binders, stabilizers, rheology modifiers, and other additives, including one or more of alumina, silica, non-zeolite silica alumina, titanium dioxide, zirconium oxide, and cerium dioxide. These non-catalytic compositions are present in the catalyst composition but are used for one or more non-catalytic purposes. For embodiments in which the molecular sieve in the catalyst contains Ce, the corresponding support coating may further comprise a binder containing Ce or cerium dioxide. For such embodiments, the Ce-containing particles in the binder are significantly larger than the Ce-containing particles in the catalyst.

[0089] In some embodiments, the catalyst support coating composition may include pore-forming agents such as graphite, cellulose, starch, polyacrylate, and polyethylene. These additional components do not necessarily catalyze the desired reaction, but rather improve the effectiveness of the catalytic material, for example, by increasing its operating temperature range, increasing the catalyst's contact surface area, or increasing the catalyst's adhesion to the substrate.

[0090] The two most common substrate designs on which catalysts can be applied are plates and honeycomb structures. Preferred substrates, particularly for mobile applications, include flow-through monoliths with a so-called honeycomb geometry, comprising multiple adjacent parallel channels that are open at both ends and typically extend from the inlet to the outlet face of the substrate, resulting in a high surface area to volume ratio. For some applications, the honeycomb flow-through monolith preferably has a high pore density (e.g., about 600 pores / square inch to 800 pores / square inch) and / or an average inner wall thickness of about 0.18 mm to 0.35 mm, preferably about 0.20 mm to 0.25 mm. For some other applications, the honeycomb flow-through monolith preferably has a low pore density of about 150 pores / square inch to 600 pores / square inch, more preferably about 200 pores / square inch to 400 pores / square inch. Preferably, the honeycomb monolith is porous. Besides cordierite, silicon carbide, silicon nitride, ceramics, and metals, other materials that can be used as substrates include aluminum nitride, silicon nitride, aluminum titanate, α-alumina, mullite (e.g., acicular mullite), cesium garnet, cermets (such as Al2O3 / Ni, Al2O3 / Ni, or B4C2Fe), or composites containing segments of any two or more of these. Preferred materials include cordierite, silicon carbide, and aluminum titanate.

[0091] Wall-flow substrates have permeable porosity and pore size, but trap most of the particulate matter (such as soot) from the gas as it passes through the wall. Preferred wall-flow substrates are high-efficiency filters. Wall-flow filters used with the present invention preferably have an efficiency of at least 70%, at least about 75%, at least about 80%, or at least about 90%. In some embodiments, the efficiency will be about 75% to about 99%, about 75% to about 90%, about 80% to about 90%, or about 85% to about 95%. Here, efficiency is relative to soot and other particles of similar size, as well as the particle concentration typically present in conventional diesel engine exhaust. For example, the size of particles in diesel exhaust can range from 0.05 micrometers to 2.5 micrometers. Therefore, efficiency can be based on this range or subranges, such as 0.1 micrometers to 0.25 micrometers, 0.25 micrometers to 1.25 micrometers, or 1.25 micrometers to 2.5 micrometers.

[0092] Preferred wall-flow filters have a porosity of about 30% to about 80%, for example, about 40% to about 75%, about 40% to about 65%, or about 50% to about 60%. Porosity is a measure of the percentage of vacant space in a porous substrate and is related to the back pressure in an exhaust system: generally, the lower the porosity, the higher the back pressure.

[0093] Preferred wall-flow filters also have at least about 30%, more preferably at least about 40%, of pore interconnection volume. Pore interconnection, measured as a percentage of the total void volume of the substrate, is the degree to which pores, voids, and / or channels engage to form a continuous path through the porous substrate (i.e., from the inlet face to the outlet face). In contrast to pore interconnection is the sum of the volume of closed pores and the volume of pores having only one channel leading to one surface of the substrate.

[0094] The average pore size of the preferred wall-flow filter is also important for filtration. The average pore size can be determined by any acceptable method, including mercury porosimetry. The average pore size of the porous substrate should be high enough to promote low back pressure while providing sufficient efficiency through the substrate itself, by promoting a dust cake layer on the substrate surface, or a combination of both. Preferred average pore sizes of the porous substrate are from about 10 μm to about 40 μm, for example, from about 20 μm to about 30 μm, from about 10 μm to about 25 μm, from about 10 μm to about 20 μm, from about 20 μm to about 25 μm, from about 10 μm to about 15 μm, and from about 15 μm to about 20 μm.

[0095] Compared to honeycomb structures, plate catalysts offer lower pressure drops and are less prone to clogging and fouling, which is advantageous in high-efficiency stationary applications; however, plate configurations can be much larger and are more expensive. Honeycomb configurations are typically smaller than plate configurations, which is advantageous in mobile applications, but they have higher pressure drops and are more susceptible to clogging. In some embodiments, the plate substrate is made of metal, preferably corrugated metal.

[0096] A method for manufacturing a catalyst article is also provided. In one specific embodiment, the catalyst article is produced by a method comprising the following steps: applying a JMZ-12 catalyst composition, preferably as a carrier coating, to a substrate as a layer or region. The carrier coating may be applied to a suitable substrate as a surface coating, a coating permeating part of the substrate, a coating permeating the substrate, or some combination thereof. Before or after applying the JMZ-12 zeolite catalyst carrier coating to the substrate, one or more additional layers of another composition for treating waste gases may be applied to the substrate. One or more catalyst layers on the substrate, together with the JMZ-12 catalyst, are arranged in full or partial layers, continuous layers, or regions (such as front and rear regions). As used herein, the term "continuous" relative to catalyst layers on the substrate means that each layer is in contact with its adjacent layer, and that the catalyst layers are arranged as a whole, overlapping each other on the substrate.

[0097] JMZ-12 catalyst can be disposed as a first layer or zone on the substrate, and another composition such as an oxidation catalyst, a reduction catalyst, a scavenging component, or NO can be disposed of. x The storage components are set on the substrate as a second layer or region.

[0098] Generally, the preparation of an extruded solid matrix containing a JMZ-12 catalyst, such as a honeycomb flow-through filter or a wall-flow filter, involves blending the JMZ-12 catalyst, a binder, and optionally an organic viscosity-enhancing compound into a homogeneous paste, and then adding the homogeneous paste to one or more of the binder / matrix component or its precursor, and optionally stabilizing cerium dioxide and inorganic fibers. The blend is compacted in a mixing or kneading device or an extruder. The mixture contains organic additives such as binders, pore-forming agents, plasticizers, surfactants, lubricants, and dispersants as processing aids to enhance wetting, thereby producing a homogeneous batch. The resulting plastic material is then molded, particularly using an extruder or extruder including an extrusion die, and the resulting molded part is dried and calcined. The organic additives are “burned off” during the calcination of the extruded solid matrix. The JMZ-12 catalyst may also be coated or otherwise applied to the extruded solid matrix as one or more sublayer carriers, which reside on the surface or are wholly or partially penetrated into the extruded solid matrix. Preferably, the JMZ-12 zeolite catalyst is dispersed throughout, and more preferably uniformly dispersed throughout the entire extruded catalyst body.

[0099] When any of the extruded solids described above is used to make a wall-flow filter, the porosity of the wall-flow filter can be 30%-80%, such as 40%-70%. Porosity, pore volume, and pore radius can be measured, for example, using mercury intrusion porosimetry.

[0100] The JMZ-12 zeolite catalyst described herein promotes the reaction of a reducing agent (preferably ammonia) with nitrogen oxides to selectively form elemental nitrogen (N2) and water (H2O). Therefore, in one embodiment, the catalyst can be formulated to facilitate the reduction of nitrogen oxides with a reducing agent (i.e., an SCR catalyst). Examples of such reducing agents include hydrocarbons (e.g., C3-C6 hydrocarbons) and nitrogen-containing reducing agents such as ammonia and hydrazine ammonia or any suitable ammonia precursor such as urea ((NH2)2CO), ammonium carbonate, ammonium carbamate, ammonium bicarbonate, or ammonium formate. Preferably, the catalyst has low N2O selectivity. N2O selectivity is defined as the number of moles of N2O formed divided by the amount of NO converted. x Number of moles (NO) x Defined as NO and NO2). Lower N2O selectivity is desirable because it is necessary to reduce N2O formation.

[0101] The JMZ-12 catalyst described herein can also promote the oxidation of ammonia. Therefore, in another embodiment, the catalyst can be formulated to facilitate the oxidation of ammonia with oxygen, particularly at ammonia concentrations typically encountered downstream of SCR catalysts (e.g., ammonia oxidation (AMOX) catalysts, such as ammonia leakage catalysts (ASC)). In some embodiments, the JMZ-12 zeolite catalyst is disposed as a top layer on an oxidation lower layer, wherein the lower layer comprises a platinum group metal (PGM) catalyst or a non-PGM catalyst. Preferably, the catalyst components in the lower layer are disposed on a high surface area support, which includes, but is not limited to, alumina.

[0102] This invention includes ASC, wherein SCR and AMOX operations can be performed in series, wherein both methods utilize a catalyst comprising the JMZ-12 catalyst described herein, and wherein the SCR method occurs upstream of the AMOX method. For example, the SCR formulation of the catalyst can be disposed on the inlet side of the filter, and the AMOX formulation of the catalyst can be disposed on the outlet side of the filter.

[0103] The present invention may include an ASC catalytic article having: a substrate having an inlet and an outlet; a first coating comprising a blend of: (1) platinum on a support, and (2) a first SCR catalyst comprising JMZ-12; and a second coating comprising a second SCR catalyst, which may be JMZ-12 or another metal-supported zeolite, such as copper CHA, copper AEI, iron CHA, or iron AEI; wherein the support comprises at least one of a molecular sieve or a mixed oxide of SiO2-Al2O3.

[0104] The second coating of the ASC completely overlaps the first coating. In some embodiments, the second coating partially overlaps the first coating. In some embodiments, the second coating extends from the inlet end toward the outlet end, covering less than the full length of the substrate. In some embodiments, the first coating extends from the outlet end toward the inlet end, covering less than the full length of the substrate. In some embodiments, the second SCR catalyst is located on the inlet side of the coating comprising the blend of platinum on the support and the first SCR catalyst. In some embodiments, the second SCR catalyst is located on the outlet side of the coating comprising the blend of platinum on the support and the first SCR catalyst.

[0105] Platinum is present in amounts of at least one of the following: (a) 0.01 wt% to 0.3 wt%; (b) 0.03 wt% to 0.2 wt%; (c) 0.05 wt% to 0.17 wt%; and (d) 0.07 wt% to 0.15 wt%, including the end values, relative to the weight of the platinum support in the blend + the weight of the platinum + the weight of the first SCR catalyst. The weight ratio of the first SCR catalyst to the platinum on the support may be in the range of at least one of the following: (a) 0:1 to 300:1, (b) 3:1 to 300:1, (c) 7:1 to 100:1; and (d) 10:1 to 50:1, including the end values.

[0106] The blends in ASC also contain at least one of palladium (Pd), gold (Au), silver (Ag), ruthenium (Ru), or rhodium (Rh).

[0107] Suitable substrates for ammonia leakage catalysts may include cordierite, highly porous cordierite, metal substrates, extruded SCRs, filters, or SCRFs.

[0108] Accordingly, the present invention provides a method for reducing NO in gases. x A method for reacting NH3 in compounds and / or oxidizing gases, the method comprising reacting the gas with NH3 as described herein for the catalytic reduction of NO. x The catalytic composition of the compound contacts and sustains a reaction sufficient to reduce NO in the gas. x The time of compound and / or NH3 levels. In some embodiments, a catalyst article is provided having an ammonia leakage catalyst disposed downstream of a selective catalytic reduction (SCR) catalyst. In such embodiments, the ammonia leakage catalyst oxidizes at least a portion of any nitrogen-containing reducing agent not consumed by the selective catalytic reduction process. For example, in some embodiments, the ammonia leakage catalyst is disposed on the outlet side of a wall-flow filter, and the SCR catalyst is disposed on the upstream side of the filter. In some other embodiments, the ammonia leakage catalyst is disposed downstream of a flow-through substrate, and the SCR catalyst is disposed upstream of the flow-through substrate. In other embodiments, the ammonia leakage catalyst and the SCR catalyst are disposed on separate blocks within the exhaust system. These separate blocks may be adjacent to and in contact with each other, or separated by a specific distance, provided that they are in fluid communication with each other and provided that the SCR catalyst block is disposed upstream of the ammonia leakage catalyst block.

[0109] The SCR and / or AMOX method is preferably carried out at a temperature of at least 150°C, for example, about 150°C to about 750°C, about 175°C to about 550°C, about 175°C to about 400°C, about 450°C to about 900°C, and more preferably about 450°C to about 750°C, about 450°C to about 650°C, or about 450°C to about 550°C. Utilizing temperatures greater than 450°C is particularly useful for treating exhaust gases from heavy-duty and light-duty diesel engines equipped with exhaust systems including (optionally catalytically catalytic) diesel particulate filters, which are actively regenerated, for example, by injecting hydrocarbons into the exhaust system upstream of the filter, wherein the zeolite catalyst used in this invention is located downstream of the filter.

[0110] Furthermore, the method of the present invention may include one or more of the following steps: (a) accumulating and / or burning soot that comes into contact with the inlet of the catalytic filter; (b) introducing a nitrogen-containing reducing agent into the exhaust gas stream before contacting the catalytic filter, preferably in the absence of NO treatment. x In the case of intermediate catalytic steps with reducing agents; (c) via NO x Adsorbent catalyst or dilute NO x The trap generates NH3, and preferably uses such NH3 as a reducing agent in the downstream SCR reaction; (d) the exhaust gas stream is contacted with DOC to oxidize hydrocarbon-based soluble organic fractions (SOF) and / or carbon monoxide to CO2, and / or oxidize NO to NO2, which can then be used to oxidize particulate matter in the particulate filter; and / or reduce particulate matter (PM) in the exhaust gas; (e) in the presence of a reducing agent, the exhaust gas is contacted with one or more flow-through SCR catalyst units to reduce NO in the exhaust gas. x Concentration; and (f) contacting the exhaust gas with the ammonia-leaking catalyst, preferably downstream of the SCR catalyst, to oxidize most (if not all) of the ammonia before the exhaust gas enters the atmosphere, or to pass the exhaust gas through the recirculation loop before it enters / re-enters the engine.

[0111] In some aspects, the present invention is a system for treating exhaust gases produced by combustion processes, such as those from internal combustion engines (whether mobile or stationary), gas turbines, coal-fired or oil-fired power plants, etc. Such systems include a catalytic article comprising the JMZ-12 catalyst described herein and at least one additional component for treating the exhaust gases, wherein the catalytic article and the at least one additional component are designed to function as coherent units. The system may include a catalytic article comprising the JMZ-12 catalyst described herein, a conduit for guiding the flow of exhaust gases, and a nitrogen-containing reducing agent source disposed upstream of the catalytic article. The system may include a method for catalyzing NO only when it is determined that the zeolite catalyst is capable of catalyzing NO at an efficiency equal to or greater than desired, such as above 100°C, above 150°C, or above 175°C.x The controller meteres the nitrogen-containing reducing agent into the flowing exhaust gas only during reduction. The metering of the nitrogen-containing reducing agent can be arranged such that 60% to 200% of the theoretical ammonia is present in the exhaust gas entering the SCR catalyst, calculated as 1:1 NH3 / NO and 4:3 NH3 / NO2.

[0112] In another embodiment, the system includes an oxidation catalyst (e.g., a diesel oxidation catalyst (DOC)) for oxidizing nitrogen monoxide in exhaust gas to nitrogen dioxide, which may be located upstream of the point where a nitrogen-containing reducing agent is metered into the exhaust gas. In one embodiment, the oxidation catalyst may be adapted to generate a gas stream entering the SCR zeolite catalyst, the gas stream having, for example, a NO to NO2 ratio of about 4:1 to about 1:3 by volume at an exhaust gas temperature of 250°C to 450°C at the oxidation catalyst inlet. The oxidation catalyst may include at least one platinum group metal (or some combination thereof), such as platinum, palladium, or rhodium, coated on a flow-through monolithic substrate. In one embodiment, the at least one platinum group metal is platinum, palladium, or a combination of both platinum and palladium. The platinum group metal may be supported on a high surface area carrier coating component such as alumina, zeolite such as aluminosilicate zeolite, silica, non-zeolite silica alumina, cerium dioxide, zirconium oxide, titanium dioxide, or a mixed or composite oxide comprising both cerium dioxide and zirconium oxide.

[0113] In another embodiment, a suitable filter substrate is located between the oxidation catalyst and the SCR catalyst. The filter substrate can be any of those described above, such as a wall-flow filter. When the filter is catalyzed, for example, with an oxidation catalyst of the type described above, the point for metering the nitrogen-containing reducing agent is preferably located between the filter and the zeolite catalyst. Alternatively, if the filter is uncatalyzed, the device for metering the nitrogen-containing reducing agent may be located between the oxidation catalyst and the filter.

[0114] Example

[0115] Examples 1 to 5: Zeolites of different members of the JMZ-12 family were synthesized using a mixture of two structure-directing agents (SDA) including N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (3,5-DMDMPOH) and tetraethylammonium hydroxide (TEAOH).

[0116] An aqueous reaction mixture was prepared comprising FAU zeolite and Na2O as an alumina source and a silica source, respectively, in a molar ratio of 68SiO2:1Al2O3:19.5Na2O:750H2O, and further comprising SDA of both 3,5-DMDMPOH and TEAOH in the molar ratio shown in Table 1.

[0117] Table 1

[0118]

[0119] Table 1 shows the synthesis and characterization data of selected JMZ-12 samples with different AEI / CHA co-occurrences, prepared by adjusting the ratio of 3,5-DMDMPOH and TEAOH. The AEI / CHA ratio was determined by DIFFaX analysis of X-ray diffraction patterns collected on the dehydrated H- form of each sample. The silica-to-alumina ratio (SAR) and micropore volume were measured by X-ray fluorescence (XRF) and Ar adsorption isotherms, respectively.

[0120] The reagents used and the order of addition are as follows:

[0121] a) Commercially available FAU zeolite

[0122] b)H2O

[0123] c) NaOH solution, 30 wt%

[0124] d) Tetraethylammonium hydroxide (TEAOH), 35% by weight

[0125] e) N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (3,5-DMDMPOH), 47% by weight.

[0126] f) Sodium silicate

[0127] In a typical embodiment, 34.700 g of commercially available FAU (Al₂O₃ = 18.49 wt%, SiO₂ = 59.65 wt%, Na₂O = 0.14 wt%) was mixed with 226 mL of water under stirring. Then, 19.05 g of NaOH (30 wt%), 58.54 g of TEAOH (35 wt%), 74.55 g of 3,5-DMDMPOH (47 wt%), and 833.26 g of sodium silicate solution (Na₂O wt% = 8.60 wt%, SiO₂ = 28.4 wt%) were added sequentially to this mixture to obtain a synthetic gel with a molar gel composition of 68.1 SiO₂ – 1.0 Al₂O₃ – 19.5 Na₂O – 3.5 3,5-DMDMPOH – 2.2 TEAOH – 750.1 H₂O.

[0128] After stirring the mixture for 1 hour, the gel was transferred to a 1.5 L autoclave and heated at 120 °C with rotation (300 rpm) for 48 hours. At the end of the reaction time, the contents of the autoclave were filtered and washed with demineralized water. The resulting product was dried overnight at 110 °C. X-ray diffraction (XRD) patterns were obtained for each powder sample (see [reference]). Figure 1XRD indicates that the product is a symbiotic of the AEI / CHA zeolite structure (JMZ-12), with varying degrees of symbiosis depending on the molar ratio of organic templates in the gel. Figure 2 The crystal morphology of the sample is shown, and Figure 3 One of the materials 13 The C magic angle rotation nuclear magnetic resonance (MAS NMR) spectrum shows that both SDAs were still contained in the sample at the end of crystallization. Figure 4 The surface silica to alumina ratio (SAR) is shown as determined by synchrotron X-ray photoelectron spectroscopy (SR-XPS). In-depth analysis of JMZ-12 reveals the difference between the bulk SAR and surface SAR of the crystal.

[0129] The prepared zeolite was activated by calcination in air. The solid was heated to 110°C at a rate of 2°C / min, then to 450°C at a rate of 5°C / min, and held at 450°C for 16 hours. Finally, the material was heated to 550°C at a rate of 5°C / min and held at 550°C for 16 hours. Once the solid cooled to room temperature, it was ion-exchanged with 1M ammonium sulfate solution using 10 ml / g of calcined zeolite. Ion exchange was carried out at room temperature with stirring for 1 hour. Stirring was stopped and the slurry was centrifuged. The clear supernatant was decanted. The ion exchange process was then repeated, followed by filtration, washing, and drying of the zeolite. The NH4- form of the zeolite was converted to the H- form by calcination in air, heating to 150°C at a rate of 2°C / min and holding at 150°C for 10 hours, then heating to 450°C at a rate of 5°C / min and finally holding at 450°C for 16 hours. The XRD pattern of the selected active material is shown in [Figure number missing]. Figure 5 The structures of pure-phase AEI and CHA zeolites were compared. Table 1 above summarizes the SAR of the selected samples as measured by XRF and their micropore volumes as measured by Ar adsorption isotherms. The AEI / CHA ratio was determined by DIFFaX analysis of the X-ray diffraction patterns collected on the dehydrated H- form of each sample. Figure 6 The XRD pattern of a physical mixture of AEI / CHA zeolite is shown compared to the XRD pattern of JMZ-12 zeolite with an AEI / CHA coexistence ratio of 50 / 50.

[0130] Example 6: Selective Catalytic Reduction (SCR) Performance (Fresh)

[0131] JMZ-12 zeolite was synthesized according to the method described herein (activated in Example 2, H-form). This zeolite has an SAR of 16. The zeolite was metal-impregnated using the desired amount of copper(II) acetate dissolved in demineralized water. The metal-impregnated zeolite was dried overnight at 80°C and then calcined in air at 550°C for 4 hours. Copper was added to the zeolite to obtain JMZ-12 having 3.3% copper by weight based on the total weight of the zeolite.

[0132] Granular samples of copper JMZ-12 zeolite were placed in the test apparatus. To evaluate the SCR performance of the zeolite over a temperature range, the zeolite was subjected to a simulated diesel engine exhaust gas flow with the following properties: 500 ppm NH3, 500 ppm NO, 0 ppm NO2, and SV = 90 K h. -1 The sample was heated from room temperature to 150°C in the aforementioned gas mixture (except for NH3). At 150°C, NH3 was added to the gas mixture, and the sample was maintained under these conditions for 30 minutes. The temperature was then increased from 150°C to 500°C at a rate of 5°C / min. Downstream gases after zeolite treatment were monitored to determine NO. x Conversion rate and N2O selectivity. For comparison, similar tests were performed on CHA zeolite with a SAR of 22 and AEI zeolite with a SAR of 20, each having a copper loading comparable to that of copper JMZ-12.

[0133] like Figure 7 As shown, compared with copper AEI zeolite and copper CHA zeolite, copper JMZ-12 obtained higher NO at temperatures above 400°C. x Conversion rate. For example... Figure 8 As shown, copper JMZ-12 exhibits equal or lower N2O selectivity across the entire temperature range (150°C to 500°C) compared to copper AEI zeolite or copper CHA zeolite. Therefore, the copper JMZ-12 catalyst demonstrates better N2O selectivity than typical Cu-exchanged CHA or AEI zeolites. x It exhibits significant advantages in both conversion rate and N2O selectivity.

[0134] Examples 7 and 8: Selective Catalytic Reduction (SCR) Performance (Aging)

[0135] A group of copper JMZ-12 zeolite, copper AEI zeolite, and copper CHA zeolite samples, similar to those in Example 6, were prepared and then hydrothermally aged at 750°C for 80 hours in air containing 10% H2O by volume. The samples of powdered catalyst were granulated and then heated from room temperature to 250°C in air only at a rate of 10°C / min. The samples were then heated to 750°C in air with 10% H2O (by volume) at a rate of 10°C / min. After holding at 750°C for 80 hours, the samples were cooled in a steam / air mixture until the temperature was below 250°C. The samples were then cooled from 250°C to room temperature in an air stream only. These samples were tested on an apparatus under conditions similar to those described in Example 6.

[0136] Another group of copper JMZ-12 zeolite, copper AEI zeolite, and copper CHA zeolite samples, similar to those in Example 6, were prepared and then hydrothermally aged at 900°C for 5 hours in air containing 4.5% H2O by volume. The samples of the powdered catalyst were granulated and then heated from room temperature to 250°C in air only at a rate of 10°C / min. The samples were then heated to 900°C in air with 4.5% H2O (by volume) at a rate of 10°C / min. After holding at 900°C for 5 hours, the samples were cooled in a steam / air mixture until the temperature was below 250°C. The samples were then cooled from 250°C to room temperature in an air stream only. These samples were tested on the apparatus under conditions similar to those described in Example 6.

[0137] like Figure 9 and Figure 10 As shown, copper JMZ-12 samples aged at 750℃ and 900℃ respectively had similar or higher NO content compared to similarly aged copper AEI zeolite and copper CHA zeolite. x Conversion performance. These results are surprising because AEI and CHA zeolites with relatively high SAR are expected to be more hydrothermally stable compared to copper JMZ-12, which has relatively low SAR. Furthermore, Figure 11 The data show that copper JMZ-12 aged at 750°C exhibits lower N2O selectivity over the entire temperature range (150°C to 500°C) compared to copper AEI zeolite or copper CHA zeolite aged under similar conditions. These results demonstrate that the catalyst of the present invention, JMZ-12, is hydrothermally stable. Furthermore, compared to copper-supported AEI or CHA, copper-supported JMZ-12 exhibits better N2O selectivity as a NO... x The benefits of eliminating catalysts.

[0138] Example 9: Selective Catalytic Reduction (SCR) Performance (Aging)

[0139] NO similar to that described in Example 8 (aging at 900°C) for copper JMZ-12 x The conversion performance and N2O selectivity were compared with those of AEI zeolites with similar SAR values ​​and loaded with copper. Figure 12 and Figure 13 As shown, compared to copper-loaded AEI zeolites, copper JMZ-12, which has an SAR of 16 and is aged at 900°C, achieved higher NO content over the entire temperature range (150°C to 500°C). x The conversion rate and N2O selectivity were low. Furthermore, both copper AEI zeolites with a SAR of 16.9 and 14.6 exhibited significant performance degradation after hydrothermal aging at 900 °C. These results demonstrate that copper-supported JMZ-12 is superior to copper-supported AEI zeolites as a NOx elimination catalyst.

[0140] Example 10: Selective Catalytic Reduction (SCR) Performance in the Presence of Rare Earth Metals JMZ-12 zeolite was synthesized according to the method described herein (activated in Example 5, H-form). This zeolite had a SAR of 16.7. The zeolite was ion-exchanged with 0.1 M yttrium(III) nitrate solution using 80 mL of solution per gram of zeolite. The ion exchange was carried out under hydrothermal conditions at 130 °C for 8 hours. The clear supernatant was decanted, and the solid product was washed and dried. Yttrium was added to the zeolite to obtain JMZ-12 with 1.1 wt% yttrium based on the total weight of the zeolite.

[0141] The yttrium-containing zeolite was then impregnated with copper using the required amount of copper(II) dissolved in demineralized water. The metal-impregnated zeolite was dried at 105°C for 3 hours and then calcined in air at 500°C for 2 hours. Copper was added to the zeolite to obtain JMZ-12 with 3.0% copper by weight based on the total weight of the zeolite.

[0142] To evaluate the SCR performance of zeolite, copper- and yttrium-containing JMZ-12 zeolite was granulated, placed in a test apparatus, and subjected to a simulated diesel engine exhaust gas with the following properties: 550 ppm NH3, 500 ppm NO, 0 ppm NO2, 10% H2O, 8% O2, and SV = 90 K h. -1 The sample was heated from room temperature to 150°C under nitrogen atmosphere, and then exposed to the above gas mixture for 1 minute. The temperature was then increased from 150°C to 500°C at a rate of 5°C / min. Downstream gases after zeolite treatment were monitored to determine NO. x Conversion rate and N2O selectivity. For comparison, similar tests were performed on JMZ-12 zeolite (Example 5) containing the same amount of copper (3.0 wt%).

[0143] like Figure 14As shown, compared to copper yttrium JMZ-12, copper JMZ-12 achieved higher NO levels across the entire temperature range. x Conversion rate. For example... Figure 15 As shown, yttrium-containing JMZ-12 exhibits better N2O selectivity within the temperature range (200°C to 300°C).

[0144] The same group of copper, yttrium, and copper JMZ-12 were also hydrothermally aged for 16 hours at 850°C in air containing 10% H2O by volume. For example... Figure 14 As shown, in the low-temperature range below 250°C, yttrium-containing JMZ-12 achieved higher NO content compared to JMZ-12. x Conversion rate. For example... Figure 15 As shown, within the same temperature range, yttrium-containing JMZ-12 exhibits similar N2O selectivity compared to JM-12.

[0145] These results demonstrate the use of yttrium-containing copper JMZ-12 to improve low-temperature NO x Elimination catalyst is superior to copper JMZ-12 zeolite.

Claims

1. A method for synthesizing zeolites, the method comprising the step of heating a reaction mixture under crystallization conditions for a sufficient period of time to form a disordered zeolite having both CHA and AEI topologies, wherein the reaction mixture comprises: a. At least one aluminum source, b. At least one silicon source, c. Alkali or alkaline earth cation source d. A structure-directing agent comprising at least one quaternary ammonium cation source and at least one alkyl-substituted piperidinium cation source in a molar ratio of 0.20 to 1.4, and e. Contains virtually no halides. The quaternary ammonium source is tetraethylammonium hydroxide, and the alkyl-substituted piperidinium source is N,N-dimethyl-3,5-dimethylpiperidinium hydroxide.

2. The method of claim 1, wherein the reaction mixture is substantially free of phosphorus.

3. The method according to claim 1, wherein the reaction mixture has the following molar composition: a. The SiO2 / Al2O3 ratio is 10 to 100; b. The X2O / SiO2 ratio is 0.01 to 0.5; c. The SDA / SiO2 ratio is 0.01 to 0.5; The d.OH / SiO2 ratio is 0.1 to 0.9; The H2O / SiO2 ratio is between 3 and 25, and Where X = Na, K, Cs, Li.

4. The method according to claim 1, wherein the reaction mixture has the following molar composition: a. The SiO2 / Al2O3 ratio is 55 to 75; b. The X2O / SiO2 ratio is 0.01 to 0.3; c. The SDA / SiO2 ratio is 0.05 to 0.2; The d.OH / SiO2 ratio is 0.6 to 0.8; The H2O / SiO2 ratio is 5 to 15, and Where X = Na, K, Cs, Li.

5. The method according to claim 1, further comprising a subsequent calcination step performed in an oxygen-containing atmosphere.

6. The disordered zeolite synthesized by the method according to claim 1, wherein the CHA and AEI topologies are the main phases, and the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:

95.

7. A disordered zeolite, said disordered zeolite comprising: a. The main phase of CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:95; and b. d50 crystal size from 0.05 micrometers to 0.25 micrometers, and d90 crystal size less than 0.5 micrometers.

8. The disordered zeolite according to claim 7, wherein the disordered zeolite is a symbiotic structure of AEI and CHA topologies.

9. The disordered zeolite according to claim 8, wherein the disordered zeolite has a main silica to alumina ratio of 10 to 25.

10. The disordered zeolite according to claim 9, wherein the disordered zeolite has a surface layer silica to alumina ratio up to 10 nm deep, the surface layer silica to alumina ratio being 40% to 95% of the bulk silica to alumina ratio.

11. A disordered zeolite, said disordered zeolite comprising: a. The main phase of CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:95; and b. CHA-rich surface topology and AEI-rich internal topology.

12. A disordered zeolite, said disordered zeolite comprising: a. The main phase of CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:95; and b. The ratio of surface silica to alumina to a depth of up to 10 nm and the ratio of bulk silica to alumina, wherein the ratio of surface silica to alumina is 5% to 60% lower than the ratio of bulk silica to alumina.

13. A method for NO x A selective reduction catalyst composition, the catalyst composition comprising: a. A disordered AEI / CHA zeolite, JMZ-12, having a main phase with CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:95, have a d50 crystal size of less than 0.5 micrometers, and have a silica to alumina ratio of 10 to 25; and b. One or more exchangeable transition metals selected from copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), molybdenum (Mo), and zinc (Zn). The zeolite and one or more exchanged transition metals are present in a weight ratio of 100:1 to 20:

1.

14. The catalyst composition according to claim 13, further comprising: a. exchanged cerium; and b. One or more rare earth metals selected from yttrium and erbium. The zeolite and one or more rare earth metals are present in a weight ratio of 2000:1 to 20:

1.

15. The catalyst composition of claim 14, wherein a majority of the one or more transition metals and a majority of the cerium are contained within a zeolite surface layer extending from one or more crystal surfaces to a depth of 0.02 micrometers.

16. A catalyst article, said catalyst article comprising: a. Multiple walls of a honeycomb structure flow-through substrate or wall-flow filter; and b. A disordered AEI / CHA zeolite catalyst, JMZ-12, coated on and / or within at least a portion of the wall, wherein i. The JMZ-12 has a main phase with CHA and AEI topologies, wherein the CHA and AEI topologies exist in a molar ratio of 95:5 to 5:95; ii. The JMZ-12 has a d50 crystal size of less than 0.5 micrometers and a silicon dioxide to aluminum oxide ratio of 10 to 25; and iii. One or more exchanged transition metals selected from copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), molybdenum (Mo) and zinc (Zn), wherein the zeolite and one or more exchanged transition metals are present in a weight ratio of 100:1 to 20:1.

Citation Information

Patent Citations

  • Synthesis of zeolite beta

    US5139759A

  • Silicoaluminophosphate molecular sieve

    US6812372B2

  • Chabazite-containing molecular sieve, its synthesis and its use in the conversion of oxygenates to olefins

    US7094389B2

  • Method for the synthesis of zeolite beta with diethylenetriamine

    US7704487B2

  • Synthesis of AEI zeolite

    CN104801338A